Social history of Johor migration and inter-ethnic relations during British rule 1885-1941 - Rahmat, Salbiyah; Fathil, Fauziah (IIUM Press, International Islamic University Malaysia, 2017)
This book examines how migration affects the population and the inter-ethnic relations of people in Johor during British rule from 1885 to 1941. This study also addresses the correlation between the land, the policy-makers of the Malay rulers and the British government, the migration and the people in Johor. It is thought that the British were responsible for the making-up of Johor’s plural society as well as the state’s prosperity. However, it is also imperative to rectify the role of Malay indigenous rulers in the migration process. In dealing with migration and its effects on inter-ethnic relations in Johor, one aspect to look at is the law and legal codes, especially the state’s constitution, Undang Tubuh Johor, which is the first written constitution in Malaya